Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2337/db06-1119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Exercise on AMPK Signaling in Skeletal Muscle of Subjects With Type 2 Diabetes

Abstract: Activation of AMP-activated protein kinase (AMPK) by exercise induces several cellular processes in muscle. Exercise activation of AMPK is unaffected in lean (BMI ϳ25 kg/m 2 ) subjects with type 2 diabetes. However, most type 2 diabetic subjects are obese (BMI >30 kg/m 2 ), and exercise stimulation of AMPK is blunted in obese rodents. We examined whether obese type 2 diabetic subjects have impaired exercise stimulation of AMPK, at different signaling levels, spanning from the upstream kinase, LKB1, to the puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
230
2
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(278 citation statements)
references
References 63 publications
25
230
2
11
Order By: Relevance
“…This observation suggests that the carriers of the minor alleles of T612M and 3U4898 have better control of glucose concentrations when in a hyperglycemic state, with concomitant reduction in DNA damage, leading to less inflammation (lower CRP) and thus lower prevalence of CVD. Exercise can increase expression of PPARGC1A in skeletal muscle of subjects with type 2 diabetes (14,50). We found that physical activity correlated with lower DNA damage.…”
Section: Discussionmentioning
confidence: 63%
“…This observation suggests that the carriers of the minor alleles of T612M and 3U4898 have better control of glucose concentrations when in a hyperglycemic state, with concomitant reduction in DNA damage, leading to less inflammation (lower CRP) and thus lower prevalence of CVD. Exercise can increase expression of PPARGC1A in skeletal muscle of subjects with type 2 diabetes (14,50). We found that physical activity correlated with lower DNA damage.…”
Section: Discussionmentioning
confidence: 63%
“…We and others (21,22) have shown that aerobic exercise has a dose-and intensity-related effect to increase insulin signaling and glucose transporter content in skeletal muscle. Exercise training increases insulin-stimulated glucose disposal and GLUT-4 (SLC2A4) protein content in obese patients with type 2 diabetes (22).…”
Section: Discussionmentioning
confidence: 85%
“…In skeletal muscle from lean type 2 diabetic patients [26,27] and obese participants [28], AMPK signalling in response to aminoimidazole carboxamide ribonucleotide (AICAR) or exercise appeared to be unchanged, although some studies have noticed modest reductions [29,30]. Thus, it is currently not clear whether a reduction in AMPK causes accumulation of skeletal muscle lipids and insulin resistance with obesity.…”
Section: Introductionmentioning
confidence: 99%